GAMBARAN MANAJEMEN PENGELOLAAN OBAT, ALAT KESEHATAN DAN BAHAN MEDIS HABIS PAKAI DI KLINIK PERISAI HUSADA BANDUNG - Ida Erna Widiyawati,; Dewi Handayani, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
Preliminary observations showed the problem of several drug items that were empty and unused, resulting in expired drugs at the Main Clinic of Perisai Husada, Bandung. The purpose of the study was to determine whether the drug management was in accordance with the standards or not. Retrospective and concurrent descriptive research design. Data collection and processing based on primary and secondary data. The research is guided by Permenkes 34 of 2021 with indicators at each stage of drug management being measured using the checklist or suitability method and indicators from Pudjaningsih (1996). The results showed that at several stages of drug management there were those that did not meet the standards, namely: procurement planning (not yet done), percentage of available fund allocation (not yet done), percentage of available capital from required funds (not yet done), control stage; percentage of dead stock (10.7%). The results according to the standard are the selection stage: compliance with the clinical formulary (84.99%), procurement: The highest procurement frequency during 2021 is high (> 24x/year) as many as 361 items, the frequency of invoice errors shows an average value of 100%. Frequency of delayed payments, the result (0%), the receipt stage is based on the suitability of the invoice (100%) and the accuracy of financial payments (100%), the storage stage is based on the layout suitability result (89.53%). The accuracy of the number of drugs on the card stock (100%). Percentage of warehouse arrangement system (93.38%). Withdrawal and Destruction Phase based on the value of expired drug in 2021 (0.08%). Recording on card stock (77.77%). External Report administration stage (50%).